The Value of Indocyanine Green Image-Guided Surgery in Patients with Primary Liver Tumors and Liver Metastases - Benjamin Weixler; Leonard A. Lobbes; Luis Scheiner; Johannes C. Lauscher; Sebastian M. Staubli; Markus Zuber; Dimitri A. Raptis (Life, 2023)
Introduction: Successful R0 resection is crucial for the survival of patients with primary liver cancer (PLC) or liver metastases. Up to date, surgical resection lacks a sensitive, real-time intraoperative imaging modality to determine R0 resection. Real-time intraoperative visualization with near-infrared light fluorescence (NIRF) using indocyanine green (ICG) may have the potential to meet this demand. This study evaluates the value of ICG visualization in PLC and liver metastases surgery regarding R0 resection rates. Materials and Methods: Patients with PLC or liver metastases were included in this prospective cohort study. ICG 10 mg was administered intravenously 24 h before surgery. Real-time intraoperative NIRF visualization was created with the SpectrumTM fluorescence imaging camera system. First, all liver segments were inspected with the fluorescence imaging system and intraoperative ultrasound for identification of the known tumor, as well as additional lesions, and were compared to preoperative MRI images. PLC, liver metastases, and additional lesions were then resected according to oncological principles. In all resected specimens, the resection margins were analyzed with the fluorescence imaging system for ICG-positive spots immediately after resection. Histology of additional detected lesions, as well as ICG fluorescence compared to histological resection margins, were assessed. Results: Of the 66 included patients, median age was 65.5 years (IQR 58.7–73.9), 27 (40.9%) were female, and 18 (27.3%) were operated on laparoscopically. Additional ICG-positive lesions were detected in 23 (35.4%) patients, of which 9 (29%) were malignant. In patients with no fluorescent signal at the resection margin, R0 rate was 93.9%, R1 rate was 6.1%, and R2 rate was 0% compared to an ICG-positive resection margin with an R0 rate of 64.3%, R1 rate of 21.4%, and R2 rate of 14.3% (p = 0.005). One- and two-year overall survival rates were 95.2% and 88.4%, respectively. Conclusion: The presented study provides significant evidence that ICG NIRF guidance helps to identify R0 resection intraoperatively. This offers true potential to verify radical resection and improve patient outcomes. Furthermore, implementation of NIRF-guided imaging in liver tumor surgery allows us to detect a considerable amount of additional malignant lesions.